Assessment of Risky Cornering on a Horizontal Road Curve by Improving Vehicle Suspension Performance - Vidas Žuraulis; Vytenis Surblys (The Baltic Journal of Road and Bridge Engineering)
Vehicle stability during cornering on horizontal road curves is a risky stage of travel because of additional factors acting. The main stability factor is centrifugal force, which depends on road curve sharpness and is very sensitive to driving speed usually controlled by the driver. However, the counterforce is produced at tire-road interaction, where different pavement types and states cause a wide variation of tire contact forces and vehicle stability. In the paper, the part of vehicle suspension performance while moving on a sharp horizontal road curve with different levels of pavement roughness was simulated by 14 degrees of freedom vehicle model. The model was built in MATLAB/Simulink software with available pavement roughness selection according to ISO 8608. The influence of variable suspension damping available in modern vehicles on risky cornering is analysed when a vehicle reaches the edge of the pavement with its specific roughness. Critical parameters of vehicle stability depending on road curvature, pavement roughness and driving speed are selected to assess the solutions for safe cornering.